Clinical features of allergic contact dermatitis to sandals: a case series - Gotama, Sinta; Hapsari, Yunita; Kusuma, Dinie Ramdhani (Bali Dermatology Venereology and Aesthetic Journal, 2023)
Background: Allergic contact dermatitis (ACD) is a skin inflammation caused by a type 4 delayed-type hypersensitivity reaction. One of the most common types of ACD is shoe dermatitis, characterized by pruritic or painful bilateral and symmetrical erythema, papules, vesicles, scaling, crusting, lichenification, or fissures at the site of footwear contact. Case series: We present seven patients with allergic contact dermatitis caused by rubber flip-flop sandals who presented with acute to chronic eczema and leukoderma. Patients range in age from 4 to 65 years old, with symptoms lasting from 5 months to 2 years. Two of the seven patients had a history of atopy. Conclusion: Flip-flop sandals are the most common offending footwear in Indonesian ACD patients because they are appropriate and comfortable in hot and humid climates like Indonesia. Rubber and rubber chemicals, preservatives, shoe adhesives, and leather materials are the most common offending allergens.